Within‐plant variation in reproductive investment: consequences for selection on flowering time. (6th January 2015) - Austen, E. J.; Forrest, J. R. K.; Weis, A. E.
Abstract Variation among the leaves, flowers or fruit produced by a plant is often regarded as a nuisance to the experimenter and an impediment to selection. Here, we suggest that within‐plant variation can drive selection on other plant‐level traits. We examine within‐plant variation in floral sex allocation and in fruit set and predict that such variation generates variation in male success among plants, thereby driving selection on flowering time. We tested this prediction in a simulation model estimating selection on flowering time through male fitness when floral sex allocation and/or fruit set vary directionally among flowers on plants. We parameterized the model through a quantitative literature survey of within‐plant change in sex allocation. As predicted, within‐plant variation in floral sex allocation and in fruit set probability can generate selection on flowering time through male fitness. Declining fruit set from first to last flowers on plants, as occurs in many species, selected for early flowering onset through male fitness. This result was robust to self‐incompatibility and to varying returns on male versus female investment. Selection caused by declining fruit set was strong enough to reverse the selection for late flowering that can be caused by intrafloral protandry. Our model provides testable predictions regarding selection on flowering time through male fitness. The model also establishes the intriguing possibility that within‐plant variation may influence selection on other traits, regardless of whether that variation is under selection itself.